Spintronics : from materials to devices - Fecher, Gerhard H.; Felser, Claudia (Springer Netherlands, 2013)
Spintronics is an emerging technology exploiting the spin degree of freedom and has proved to be very promising for new types of fast electronic devices. Amongst the anticipated advantages of spintronics technologies, researchers have identified the non-volatile storage of data with high density and low energy consumption as particularly relevant. This monograph examines the concept of half-metallic compounds perspectives to obtain novel solutions and discusses several oxides such as perovskites, double perovskites and CrO2 as well as Heusler compounds. Such materials can be designed and made with high spin polarization and, especially in the case of Heusler compounds, many material-related problems present in current-day 3d metal systems, can be overcome. Spintronics: From Materials to Devices provides an insight into the current research on Heusler compounds and offers a general understanding of structure-property relationships, including the influence of disorder and correlations on the electronic structure and interfaces. Spintronics devices such as magnetic tunnel junctions (MTJs) and giant magnetoresistance (GMR) devices, with current perpendicular to the plane, in which Co2 based Heusler compounds are used as new electrode materials, are also introduced. From materials design by theoretical methods and the preparation and properties of the materials to the production of thin films and devices, this monograph represents a valuable guide to both novices and experts in the fields of Chemistry, Physics, and Materials Science.